2020
DOI: 10.3390/s20102909
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence-Based Energy Transfer Using Semiconductor Quantum Dots as Acceptors

Abstract: Bioluminescence resonance energy transfer (BRET) is the non-radiative transfer of energy from a bioluminescent protein donor to a fluorophore acceptor. It shares all the formalism of Förster resonance energy transfer (FRET) but differs in one key aspect: that the excited donor here is produced by biochemical means and not by an external illumination. Often the choice of BRET source is the bioluminescent protein Renilla luciferase, which catalyzes the oxidation of a substrate, typically coelenterazine, producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Unlike fluorescence-based methods, bioluminescence systems have a broad dynamic range, high sensitivity, and operational simplicity [ 28 , 29 , 30 , 31 ]. We have previously found that the bioluminescence of Renilla luciferase (Rluc) is affected by the ionic strength [ 7 ], and hypothesized that this ionic strength effect can be extrapolated to other luciferases and used for ionic strength sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike fluorescence-based methods, bioluminescence systems have a broad dynamic range, high sensitivity, and operational simplicity [ 28 , 29 , 30 , 31 ]. We have previously found that the bioluminescence of Renilla luciferase (Rluc) is affected by the ionic strength [ 7 ], and hypothesized that this ionic strength effect can be extrapolated to other luciferases and used for ionic strength sensing.…”
Section: Introductionmentioning
confidence: 99%
“… 243 To accomplish this, the QD-DNA portion was kept essentially the same as described above except that multiple copies of a ∼36 kDA mutated Renilla reniformis luciferase enzyme (abbreviated as Luc, the enzyme responsible for bioluminescence in fireflies) were directly assembled to the QD surface in addition to the DNA wires. 247 Luc was expressed with a C-terminal (His) 6 -motif for conventional purification over Ni-chelate media and this also allowed it to self-assemble to the QDs by metal affinity coordination. Although the 540 nm emitting CdSe/CdZnS/ZnS core/shell/shell QDs (diameter 4.3 nm) utilized could accommodate an estimated maximum of 15 Luc on its surface, in experiments only 6 were used.…”
Section: Programmable Dna-based Optical Breadboardsmentioning
confidence: 99%
“…The bioluminescence resonance energy transfer (BRET) assay ( Figure 5 ) involving the use of RLuc has become popular since the late 1990s for measurements of protein–protein interactions and conformational rearrangements in live cells [ 138 , 139 , 140 ], for non-invasive bioimaging [ 141 ], and as probes for biosensing [ 123 , 142 ]. The sensitivity of BRET assays has recently been improved by introducing new BRET components: RLuc2 and RLuc8 with improved quantum yields, stability, and brightness [ 143 ] as well as a great variety of acceptors (GFP2, YFP, Venus, mOrange, TagRFP, TurboFP, semiconductor quantum dots or carbon-dots) [ 144 , 145 , 146 ]. However, the main application of RLuc is luciferase genetic reporter assay that has become an invaluable and routine tool for molecular biology research, including identification and characterization of protein functional variants [ 147 , 148 ], investigations of gene expression [ 148 , 149 , 150 ], transcription factors [ 151 , 152 , 153 , 154 , 155 ], receptor activity [ 156 ], miRNA expression [ 157 , 158 , 159 ], monitoring mRNA splicing events in cells [ 160 , 161 ], virus investigations [ 162 , 163 , 164 ], drug discovery [ 165 , 166 ], and identification and evaluation of virus inhibitors [ 167 , 168 ].…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%